Public libraries and school libraries: Major differences (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
AbstractPublic and school libraries in Brazil have not yet been universalized. Many are in a precarious state, and their functions are often confused. In order to demonstrate that such reality persists, some projects that were submitted to an Official Announcement (call for proposals), called “Construindo uma Minas Leitora” (Building an active reading Minas State), issued by the state of Minas Gerais, Brazil, for the establishment of public libraries, were selected and analyzed. Most of the projects evaluated showed that the function, target public, collection, and services offered by public and school libraries are often confused. Based on the literature and basic documents used in the formulation of the concepts of public and school libraries, it was found that the lack of public policies related to these two types of libraries leads to a vicious circle of lack of experience and knowledge in these libraries. Thus, the same precarious and inadequately structured existing models are used. Such situation, which results from the lack of public policies since the birth of the Brazilian nation, have persisted into the 21st century.Keywords: Government policy. Minas Gerais. Public libraries. School libraries.Link: http://www.scielo.br/pdf/tinf/v30n2/0103-3786-tinf-30-2-0237.pdf